2022
DOI: 10.1007/s40801-022-00318-2
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Pattern of Analgesics in Colombia. Are there Differences between Capital Cities and Municipalities? A Cross-Sectional Study

Abstract: Background Analgesics provide multiple clinical benefits but they are not without risks. Objective The aim of this study was to compare the outpatient prescribing pattern of analgesics between cities and municipalities in Colombia and to identify the variables associated with prescribing opioid analgesics. Methods This was a cross-sectional study that identified the prescription of analgesics for outpatient use from a population database of 8.5 million Colombians. A descriptive, bivariate, and multivariate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…The median age of these chronic pain patients was higher than that documented in other studies conducted in America and Europe, 8,9,12,15,16 while the predominance of women was consistent with that reported in other publications 1,5,8,9,12,15,16 . The geographical variation on analgesic drug usage has been reported previously in the country 17 . Among patients with chronic pain in Spain, Greece, Italy and the United Kingdom, the most frequently reported type of pain was of musculoskeletal origin, 3,5,18,19 consistent with the findings of this report.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The median age of these chronic pain patients was higher than that documented in other studies conducted in America and Europe, 8,9,12,15,16 while the predominance of women was consistent with that reported in other publications 1,5,8,9,12,15,16 . The geographical variation on analgesic drug usage has been reported previously in the country 17 . Among patients with chronic pain in Spain, Greece, Italy and the United Kingdom, the most frequently reported type of pain was of musculoskeletal origin, 3,5,18,19 consistent with the findings of this report.…”
Section: Discussionsupporting
confidence: 89%
“…1,5,8,9,12,15,16 The geographical variation on analgesic drug usage has been reported previously in the country. 17 Among patients with chronic pain in Spain, Greece, Italy and the United Kingdom, the most frequently reported type of pain was of musculoskeletal origin, 3,5,18,19 consistent with the findings of this report.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, it was identified that almost all of the prescriptions were made by general practitioners, which provides an opportunity to implement continuing education and therapeutic update strategies for this group of professionals, in an effort to reduce potentially inappropriate opioid prescriptions. The findings in differences between regions have been previously described in pharmacoepidemiological studies, opening opportunities for the implementation of clinical practice guidelines and updates for physicians, especially those in regions with greater formulations [ 4 , 16 , 21 ].…”
Section: Discussionmentioning
confidence: 74%
“…The most widely used opioids for pain management in this group of patients were codeine + acetaminophen and tramadol, which have already been previously described in studies in Colombia [ 20 , 21 ]. This may be explained by doctors’ ignorance about the effectiveness of various antimigraine medications and analgesics, accompanied by a feeling of greater confidence in the use of opioids for any clinical condition that causes pain [ 11 , 14 , 22 ].…”
Section: Discussionmentioning
confidence: 98%